Nanocarbon-Based Composites and Their Thermal, Electrical, and Mechanical Properties (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This Topical Collection is committed to exploring novel nanocomposite materials reinforced with carbon nanostructures for improved mechanical, thermal, and electrical properties. This Topical Collection covers the development of metallic, ceramic, and polymeric multifunctional nanocomposites through the incorporation of graphene-based materials, carbon nanotubes, fullerenes, nanodiamonds, and nanohorns. Carbon nanomaterials with different dimensions are characterized by excellent mechanical resistance, electrical and thermal conductivity, and high versatility for chemical surface functionalization. This is a critical feature for modulating their interfaces at the atomic level for improved dispersibility and compatibility with several matrices. Within this context, this Topical Collection is dedicated to manufacturing processes, simulation prediction and analysis, and structural characterization of the carbon-based nanocomposite.